From segregation to diversity: Professional identity formation among indigenous minority students - Abu-Gweder, Aref; Gribiea , Adnan (Journal of International Students, 2026)
Cultural expectations reinforce the notion that teaching is a field that balances work and family. However, unlike their Jewish peers, who have time for reflection during military service, Bedouin students transition directly from school to academia, often before their personal aspirations are clarified. This study examines the professional identity dilemmas of 30 Bedouin candidates (14 men, 16 women) at a multicultural college in Southern Israel. Using narrative questionnaires and discourse positioning analysis, this research explored the transition from segregated schooling to a diverse academic environment. The findings highlight systemic educational challenges and distinct gender-based coping strategies, with female participants demonstrating more active resilience and experiential learning.